PENGKAJIAN STABILISASI TANAH LUNAK DAN GAMBUT DENGAN MENGGUNAKAN CAIRAN E-POROUS - Affandi, Diah (JURNAL SUMBER DAYA AIR, 2018)
Soil stabilization has been used for an extensive period. Various soil properties can be improved or altered by soil stabilization. There are several techniques available by which soil properties like strength, workability, permeability and volume changes can be improved or altered. This paper examines the various techniques for soil stabilization with E-porous liquid .This test will be compared to improvement of technical parameters and physics (compressive strength, permeability and specific gravity) resulted by the mixture between soft and peat soil with fluid E porous at a percentage of 200 ml, 300 ml, 400 ml and 500 ml.